Cross‐sectional association of metrics derived from continuous glucose monitoring with cognitive performance in older adults with type 2 diabetes. Issue 1 (28th September 2022) - Sugimoto, Taiki; Tokuda, Haruhiko; Miura, Hisayuki; Kawashima, Shuji; Ando, Takafumi; Kuroda, Yujiro; Matsumoto, Nanae; Fujita, Kosuke; Uchida, Kazuaki; Kishino, Yoshinobu; Sakurai, Takashi
Abstract: Aim: To examine the association between continuous glucose monitoring (CGM)‐derived metrics and cognitive performance in older adults with type 2 diabetes (T2D). Materials and methods: A total of 100 outpatients with T2D aged 70 years or older were analysed. Participants underwent CGM for 14 days. As CGM‐derived metrics, mean sensor glucose (SG), glucose coefficient of variation (CV), time in range (TIR; 70‐180 mg/dl), time above range (TAR; > 180 mg/dl) and time below range (TBR; < 70 mg/dl), were calculated. Participants underwent cognitive tests, including the Japanese version of the Montreal Cognitive Assessment (MoCA‐J), a delayed word‐recall test from the Alzheimer's Disease Assessment Scale‐cognitive subscale, a digit symbol substitution test, a letter word fluency test, a trail‐making test (TMT) and digit span test (DSP). Results: In multiple regression analyses adjusted for confounders, a higher mean SG was associated with a lower performance in MoCA‐J and TMT part B (TMT‐B) ( P  < .05). A higher TAR was associated with a lower performance in TMT‐B and DSP‐backward ( P  < .05). By contrast, a higher TIR was associated with better function in TMT‐B and DSP‐backward ( P  < .05). Furthermore, CV and TBR were not associated with any cognitive function. Conclusion: Hyperglycaemia metrics and TIR derived from CGM are associated with cognitive functions, especially with executive function and working memory, in older adults with T2D.